Role of Digital Literacy in Transforming Pedagogical Practices of University Teachers - Anam Shehzadi; Shaiza Tanveer; Subhan Memoona (`, 2025)
The present study gives an insight into the Impact of Digital Literacy on Pedagogical Competence of University Teachers at University of Narowal. In light of extensive advances of technology, the successful use of digital tools for educational purposes plays a significant role in enriching the educational process and consequently, the degree of student achievement. The objective of this study is to investigate the current state of digital literacy in terms of faculty members, pedagogical use and the obstacles to an effective use of digital literacy. It has used the mixed method approach, quantitative and qualitative were followed to get data. A sample of 40 teachers of education” of the University of Narowal was taken by using stratified random sampling technique. Data was obtained using surveys and semi-structured interviews to understand faculty member's digital literacy, the use of technology in teaching and the challenges they encounter. The results indicate that while faculty have basic digital literacy skills, there is a gap in their capacity to implement advanced digital tools in their teaching. The lack of infrastructure, training and psychological resistance were reported as the main barriers. It also demonstrates the positive effects in terms of teaching of digital literacy on pedagogy (interest and better results of students). This study has implications for our understanding of the conditions that support the uptake of digital tools in higher education. Results highlight the importance of the respective need for targeted staff development programs, improved infrastructure and institution support to support digital literacy and teacher pedagogy. Keywords: Digital Literacy, Transforming, Pedagogical Practices, University Teachers